The Aestheticisation of Governance in India: The Appeal of Urban Aesthetics in Microfinance - Tanushree Kaushal (Revue Internationale de Politique de Développement)
Financial processes are aestheticised both spatially and in embodied modes, as urban spaces such as New Delhi change and become ‘world-class’ in response to finance and give rise to new internal urban hierarchies and figurations of the ‘ideal’ inhabitants of such cities. These processes of aestheticising financialisation 1define new modes of governance, in which state allocation of funds and resources comes to be defined around specific urbanised aesthetics, which take priority over ‘economic efficiency’ and other more conventional rationales for government decision-making. Using the case of microfinance, a rapidly financialising mode of rural credit provision in India, this chapter highlights how government entities’ underspending is shaped and rationalised by financialised aesthetics. The chapter draws upon interviews, and fieldwork involving distinct types of microfinance entities including government-based, civil-society, and private-financial, to elicit the ways in which urban finance holds sway and how evocations of urbanity shape underspending. At the intersection of finance and development, microfinance provides a case in which financialised urban aesthetics have material repercussions in terms of state allocation of funds and decisions on (withholding) spending. The chapter will discuss how the appeal of urban-financial aesthetics has material consequences that shape the fates and fortunes of both public and private entities and their capacity to secure funding, and for welfare provision.